2022
DOI: 10.2185/jrm.2021-039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 lockdown on the pathway of care and treatment outcome among patients with tuberculosis in a rural part of northern India: a community-based study

Abstract: Objectives: The coronavirus disease 2019 (COVID-19) pandemic affected routine healthcare services across all spectra, and tuberculosis (TB) care under the National Tuberculosis Elimination Program have been affected the most. However, evidence available at the community level is minimal. The clinical features, care cascade pathway, and treatment outcomes of TB patients pre- and during/post-COVID-19 pandemic lockdown in a rural community health block in northern India were assessed and compared. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Our finding that the initial phase of the COVID-19 pandemic was associated with longer delays in TB diagnosis is consistent with reports from other countries that showed that patients experienced longer overall delays during the pandemic compared to before [2][3][4][5]. In most studies that distinguished between delay before and after contact with the health system, the former was far longer than the latter; in these studies, the average delay after entering the health system was generally under a week, even during the pandemic, and overall delay was driven by the delay in accessing health services [2,3,5].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding that the initial phase of the COVID-19 pandemic was associated with longer delays in TB diagnosis is consistent with reports from other countries that showed that patients experienced longer overall delays during the pandemic compared to before [2][3][4][5]. In most studies that distinguished between delay before and after contact with the health system, the former was far longer than the latter; in these studies, the average delay after entering the health system was generally under a week, even during the pandemic, and overall delay was driven by the delay in accessing health services [2,3,5].…”
Section: Discussionsupporting
confidence: 91%
“…The global COVID-19 pandemic overwhelmed and disrupted health services worldwide, negatively impacting the delivery of TB services in many countries. Globally, there were 18% fewer TB cases diagnosed in 2020 compared to 2019 [1], and reports from diverse countries have measured significantly longer delays in TB diagnosis during the pandemic [2][3][4][5]. Modeling studies suggest that the pandemic has caused substantial increases in TB-associated mortality by delaying TB diagnoses or causing diagnoses to be missed completely [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…People were terri ed of getting COVID-19, which had a signi cant impact on TB control. It was challenging for people to get to care facilities due to the transportation constraints [47]. In order to combat COVID-19, TB laboratories and TB wards were reassigned, which also disrupted TB services due to delayed diagnosis and treatment beginning.…”
Section: Discussionmentioning
confidence: 99%
“…The study designs of the included studies were as follows; one study was described as a surveillance report [45], 12 studies were longitudinal before and after time series [15,24,[30][31][32][34][35][36][37][38][39][40], 12 were cohort studies [17,[20][21][22][27][28][29]33,[41][42][43] and the remaining three were cross-sectional studies [23,25,44]. Ten studies [17,25,26,29,31,32,34,36,37,39] had nationally representative data while others were provincial, and community based.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Ten studies [17,25,26,29,31,32,34,36,37,39] had nationally representative data while others were provincial, and community based. About six studies reported some summary measures of age [30,[33][34][35]38,40], but the other twenty-one studies did not state the age of included participants. The characteristics of the included studies are shown in Supplementary Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%